2021
DOI: 10.1016/j.htct.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect and correlation of smoking with platelet indices, neutrophil lymphocyte ratio and platelet lymphocyte ratio

Abstract: Introduction Smoking is associated with the occurrence and progression of cardiovascular diseases, inflammatory disorders and malignancies. Objective To study the platelet indices, neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) in smokers and their correlation with smoking pack-years. Method A total of 110 smokers and 110 non-smokers were included. The smokers were grouped into three groups: mild (<5 pack-years), modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
4
17
1
1
Order By: Relevance
“…From another point of the view, it is also shown that stress-related hormones such as catecholamine and cortisol are related to an increase in NLR (32). Considering that nocturnal overactivity of the hypothalamic-pituitary-adrenal system is linked to RLS/WED and related disturbed sleep, it might be a factor that contributes to increased NLR in pregnant women with RLS/WED, but further studies are needed for this conclusion (33), Also, an increase in NLR and PLR was associated with smoking (34), which was suggested to be used as a systemic infl ammatory biomarker to indicate the deleterious effects of smoking. In this term, the mechanisms by which smoking increases the risk of RLS/WED during pregnancy may be explained at least in part by infl ammation.…”
Section: Discussionmentioning
confidence: 99%
“…From another point of the view, it is also shown that stress-related hormones such as catecholamine and cortisol are related to an increase in NLR (32). Considering that nocturnal overactivity of the hypothalamic-pituitary-adrenal system is linked to RLS/WED and related disturbed sleep, it might be a factor that contributes to increased NLR in pregnant women with RLS/WED, but further studies are needed for this conclusion (33), Also, an increase in NLR and PLR was associated with smoking (34), which was suggested to be used as a systemic infl ammatory biomarker to indicate the deleterious effects of smoking. In this term, the mechanisms by which smoking increases the risk of RLS/WED during pregnancy may be explained at least in part by infl ammation.…”
Section: Discussionmentioning
confidence: 99%
“…the same result was reported by Mukta Pujani et al There was no significant difference in the NLR among the smokers and non-smokers (2.61 ± 1.99), (2.48 ± 2.30) respectively. [17].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the preoperative serum of the patients who developed sFS after RCR was sufficient to induce shoulder capsule fibrosis, which was related to its effect on macrophage polarization and fibroblast activation. NLR can be influenced by various factors, such as smoking, gender, aging et al, 44,45 therefore is hard to figure out the exact reason behind its variation among population. Instead, we directly investigated the effect of serum on shoulder capsule in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…NLR can be influenced by various factors, such as smoking, gender, aging et al, 44 , 45 therefore is hard to figure out the exact reason behind its variation among population. Instead, we directly investigated the effect of serum on shoulder capsule in a mouse model.…”
Section: Discussionmentioning
confidence: 99%